Inadvertent yellow fever vaccination of a patient with Crohn's disease treated with infliximab and methotrexate. (29th August 2016) - Ekenberg, Christina; Friis-Møller, Nina; Ulstrup, Thomas; Aalykke, Claus
Abstract : We present a case of a 56-year-old woman with Crohn's disease, treated with methotrexate and infliximab, who inadvertently received yellow fever vaccination (YFV) prior to a journey to Tanzania. She was not previously vaccinated against YF. YFV contains live-attenuated virus, and is contraindicated in patients treated with immunosuppressive drugs. Following vaccination, the patient fell ill with influenza-like illness. Elevated transaminase levels and YF viremia were detected. Despite being immunocompromised, the patient did not develop more severe adverse effects. Neutralising antibodies to YF virus were detected on day 14 following vaccination and remained protective at least 10 months after vaccination. Limited data is available on outcomes of YFV in patients receiving immunosuppressive therapy, including biologics, and we report this case as a reminder of vigilance of vaccine recommendations in this population.